Understanding the Influence of Companion Animal on Child Development: a Literature Review - Risa Juliadilla; Nia Anggri Noveni (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
Research on human-animal interaction (HAI) is a brand-new thing in Indonesia. However, it is not widely known that human-animal interactions provides positive effect to child development. The study aims to increase literacy regarding human and animal interaction that also looks at the impacts to child development. This study uses an approach of narrative review that examines and analyzes the selected eight papers. This article investigated some of the following aspects of child development in the social-emotional, cognitive and moral development associate with the interaction between children and companion animals. The analysis shows that aspects of social-emotional development assist children, improving their ability to express emotions and conduct emotional regulation. For cognitive development, helps children while interacting with animals and eases children increasing their biological knowledge about animals and children might learn the cognitive empathy related to Theory of Mind. For moral development, it helps children to act pro-social and empathy